2015
DOI: 10.1017/ice.2015.99
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Discontinuing Contact Precautions for VRE and MRSA on Device-Associated Infections

Abstract: The impact of discontinuing contact precautions for patients with MRSA and VRE colonization/infection on device-associated hospital-acquired infection rates at an academic medical center was investigated in this before-and-after study. In the setting of a strong horizontal infection prevention platform, discontinuation of contact precautions had no impact on device-associated hospital-acquired infection rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 8 publications
2
33
0
Order By: Relevance
“…Recent studies suggest that colonization with MRSA and VRE may be short-lived, even in the event of a recent infection, 8 and several have questioned the potential for nosocomial transmission. 4,7,9 In a randomized multicenter study, a universal glove and gown strategy for ICU patients did not impact the primary outcome of combined MRSA and VRE acquisition rates. 4 When employing a universal gloving and gowning strategy, more than 300 patient encounters may be required to prevent a single instance of MRSA acquisition.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Recent studies suggest that colonization with MRSA and VRE may be short-lived, even in the event of a recent infection, 8 and several have questioned the potential for nosocomial transmission. 4,7,9 In a randomized multicenter study, a universal glove and gown strategy for ICU patients did not impact the primary outcome of combined MRSA and VRE acquisition rates. 4 When employing a universal gloving and gowning strategy, more than 300 patient encounters may be required to prevent a single instance of MRSA acquisition.…”
Section: Discussionmentioning
confidence: 96%
“…10 Gown and glove use is associated with significant cost for PPE. 1,7 Several prior studies have reported substantial cost savings after the discontinuation of contact precautions for MRSA-and VRE-infected or -colonized patients. 7,11 One quasi-experimental before-and-after study demonstrated that discontinuation of contact precautions for MRSA and VRE may decrease isolation days by 45% and healthcare costs by up to $622,405 annually.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 One study showed no increase in device-associated HAI rates after discontinuing CP for MRSA/VRE. 32 …”
Section: Introductionmentioning
confidence: 99%